Обзор клещей рода Caraboacarus (Tarsonemina, Caraboacaridae) мировой фауны - Эйдельберг, М.М. (Вестник зоологии, 1993)
Close similarity of Caraboacarus karenae Nickel et Elzinga, 1969 and C. stammeri Krczal, 1959 is shown after qualitative and morphometric characters. A key to 5 known representatives of the family and distributional data are given. C. calosomcie, described from Chile, is found in Rostov region (Russia). Preference to parasitize Harpalini carabid beetles is found for C. stammeri.